Komunistična partija in njeno delovanje na Kamniškem med drugo svetovno vojno in v prvih letih po njej - Damjan Hančič (Dileme, 2018)
The contribution contains an overview of the Communist Party‘s operation in the Kamnik area as well as some consequences of its operation during the war and in the early post-war years. The analysis based on archival and other sources shows the organisation and operation of the Communist Party during the war and the consequences of its operation. This refers mainly to the victims, most of which were civilians. The article also presents the post-war repressive measures and the influence the Communist Party had over development in the early post-war years. This period is imbued with revolutionary violence and represents the toughest period of communist totalitarianism.